Laparoscopic anatomic segmentectomy 8 using the outer-Laennec approach. (December 2020) - Monden, Kazuteru; Sadamori, Hiroshi; Hioki, Masayoshi; Sugioka, Atsushi
Abstract: Background: Laparoscopic anatomic segmentectomy 8 is a difficult and technically demanding procedure owing to exposure of two major hepatic veins. To safely and accurately perform this procedure, the outer-Laennec approach was developed (Kiguchi et al., 2019) [1 ], which is based on the structure of Laennec's capsule (Sugioka et al., 2017; Laennec, 1802; Hayashi et al., 2008) [2, 3, 4 ]. The capsule comprises two layers: the hepatic and cardiac Laennec's capsules surrounding the major hepatic vein (Kiguchi et al., 2019) [1 ]. The outer-Laennec approach maintains the strength of the hepatic vein wall, preserving the two layers of Laennec's capsule. We describe a laparoscopic anatomic segmentectomy 8 using the outer-Laennec approach for hepatocellular carcinoma (HCC). Methods: Parenchymal transection was initiated to expose the root of the middle hepatic vein and right hepatic vein with the cranio-caudal view. The space between the hepatic Laennec's capsule and liver parenchyma was invaded using the outer-Laennec approach. The cavitron ultrasonic surgical aspirator was used from the root side toward the peripheral side to retain the hepatic Laennec's capsule on the vein wall and avoid splitting the bifurcation of the hepatic vein. The parenchymal dissection process was completed by an S8 Glissonean pedicle dissection. Results: The operative time was 296 min, and the estimated blood loss was 10 mL. The postoperative course was uneventful, and the patient was discharged on postoperative day 5. A pathological examination confirmed that the 2.0-cm mass was HCC with negative margins. Conclusion: The outer-Laennec approach is feasible and useful to standardize the safe laparoscopic anatomic segmentectomy 8. Highlights: Laparoscopic anatomic Segmentectomy 8 using the outer-Laennec approach. A 67-year-old man with a 20-mm hepatocellular carcinoma in the segment 8. The precise anatomy of Laennec's capsule around the hepatic vein. The procedure of the outer-Laennec approach for laparoscopic Segmentectomy 8.